Telehealth and patient satisfaction: a systematic review and narrative analysis - Kruse, Clemens Scott; Krowski, Nicole; Rodriguez, Blanca; Tran, Lan; Vela, Jackeline; Brooks, Matthew (BMJ open, 2017)
BackgroundThe use of telehealth steadily increases as it has become a viable modality to patient care. Early adopters attempt to use telehealth to deliver high-quality care. Patient satisfaction is a key indicator of how well the telemedicine modality met patient expectations.ObjectiveThe objective of this systematic review and narrative analysis is to explore the association of telehealth and patient satisfaction in regards to effectiveness and efficiency.MethodsBoolean expressions between keywords created a complex search string. Variations of this string were used in Cumulative Index of Nursing and Allied Health Literature and MEDLINE.Results2193 articles were filtered and assessed for suitability (n=44). Factors relating to effectiveness and efficiency were identified using consensus. The factors listed most often were improved outcomes (20%), preferred modality (10%), ease of use (9%), low cost 8%), improved communication (8%) and decreased travel time (7%), which in total accounted for 61% of occurrences.ConclusionThis review identified a variety of factors of association between telehealth and patient satisfaction. Knowledge of these factors could help implementers to match interventions as solutions to specific problems.